UMPSA lecturer invents I-GCPM Modular to help students deepen project management and professional certification exams - Hafizatulazlin, Abdul Aziz (UMPSA, 2023)
GAMBANG, 18 September 2023 - Researcher and senior lecturer, Faculty of Industrial Management (FPI), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Associate Professor Dr. Lee Chia Kuang, 38, conducted a research titled ‘A New Interactive Global Certified Project Management (I-GCPM) Modular’.